The mind of the terrorist the psychology of terrorism from the IRA to Al Qaeda - Post, Jerrold M. (Palgrave Macmillan, 2007)
Terrorism did not begin with 9/11. This book remembers the long history of terrorism and considers the question: what makes people terrorists? By looking into the mind of terrorists, Post sheds light on their paths to pathology and provides detailed analysis of how to combat them in the contemporary world